WSN localization scheme based on received signal strength indicator (RSSI) for zigbee networks - Idoudi, M. (2015)
The research work described here is partial work which is done with ESRG TEAM of the ALGORITHMI CENTRO in the University of Minho under the guidance of Pr. Jorge CABRAL in collaboration with Tiago Gomes and DR. Reza Abrishambaf at The University of Minho, Guimaraes. I am very thankful for them support.